1999
DOI: 10.1002/(sici)1097-4695(199908)40:2<185::aid-neu5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Motor neuron degeneration after sciatic nerve avulsion in adult rat evolves with oxidative stress and is apoptosis

Abstract: The mechanisms for motor neuron degeneration and regeneration in adult spinal cord following axotomy and target deprivation are not fully understood. We used a unilateral sciatic nerve avulsion model in adult rats to test the hypothesis that retrograde degeneration of motor neurons resembles apoptosis. By 21 days postlesion, the number of large motor neurons in lumbar spinal cord was reduced by ∼30%. The death of motor neurons was confirmed using the terminal transferase‐mediated deoxyuridine triphosphate‐biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
2
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 56 publications
6
111
2
9
Order By: Relevance
“…25 As a consequence of such lesions, the spinal motor neurons showed chromatolysis, loss of Nissl bodies, and dramatic perikarayal shrinkage, leading to apoptosis. 26 In the current study, however, no nerve lesions were involved; yet, the data revealed a series of progressive motor neuronal and axonal degenerative changes over periods of knee joint immobilization. These changes consisted of axonal demyelination, up-regulated neuronal NOS-LI, folding of nuclear envelope, and increases in nuclear chromatic density.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…25 As a consequence of such lesions, the spinal motor neurons showed chromatolysis, loss of Nissl bodies, and dramatic perikarayal shrinkage, leading to apoptosis. 26 In the current study, however, no nerve lesions were involved; yet, the data revealed a series of progressive motor neuronal and axonal degenerative changes over periods of knee joint immobilization. These changes consisted of axonal demyelination, up-regulated neuronal NOS-LI, folding of nuclear envelope, and increases in nuclear chromatic density.…”
Section: Discussionsupporting
confidence: 84%
“…For example, nitric oxide-mediated oxidative stress after nerve lesions would cause subcellular degenerative changes before neuronal death, including interruption of the integrity of mitochondria, redistribution of rough endoplasmic reticulum, shrunken nuclear envelop, and small compact clumps of chromatin. 26 Although these findings are not identical, they are similar to the findings of this study.…”
Section: Nitric Oxide-mediated Oxidative Stressmentioning
confidence: 99%
“…It is possible that APE/Ref-1 is induced in response to oxidative stress occurring during the chromatolytic stage of motor neuron degeneration. Recent studies have shown that neurons undergoing apoptosis in animal models pass through three major structural stages of degeneration: chromatolysis, somatodendritic atrophy, and apoptosis (Al-Abdulla and Martin, 1998;Martin et al, 1999;Martin and Liu, 2002). Motor neurons in ALS appear to follow this staging scheme of degeneration (Martin, 1999).…”
Section: Neuromolecular Medicinementioning
confidence: 99%
“…Formation of nitrotyrosine residues has been correlated with neurodegenerative events and has been detected in the spinal cord after ventral root avulsion [62], in transgenic mice expressing amyotrophic lateral sclerosis (ALS)-mutant SOD [63], both in upper and lower motor neurons of ASL-patients [15], and in motor neuron apoptosis [50]. The results in Fig.…”
Section: Discussionmentioning
confidence: 88%